The use of aircraft measurements to determine transport, dispersion and transformation rates of pollutants emitted from oil sands extraction plants in Alberta ... - Davis, A.; Peake, E.; Cheng, L.; Rogers, D. (University of Alberta Library, 1987)
A field program study was conducted to determine the transport, dispersion, and transformation of sulphur and nitrogen oxides emitted from oil sands extraction plants in the Fort McMurray area. Measurements using the Intera/Alberta Research Council research aircraft were made under cold winter conditions during the months of March and December 1983 and warm summer conditions during June 1984. Sulphur dioxide emissions were detected as far as 90 km downwind from the source stack. Comparisons between the observed horizontal dispersion parameters and those of the Pasqui 11-Gifford stability classes show their rates of change with distance were similur, although observed values were slightly higher than predicted ones. The rate of transformation of so2 to SO2 was determined to be 0% to 2.81% h-l in the winter and 0% to 8.66% h-in the summer. Higher summer values are attributed to greater solar irradiance. Excess aerosol volume productions suggest that heterogeneous conversion may be appreciable under certain ...